Cover Measurement Method for Middle Slabs of RC Rigid Frame Viaducts - Dobashi, Ryota; Kaneshima, Atsuki; Kobayashi, Takashi; Douchi, Yugo; Nihei, Tatsuya; 亮太, 土橋; 篤希, 金島; 小林 史; 悠吾, 堂内; 達也, 仁平 (Denki Gakkai ronbunshi. D, Sangyō ōyō bumonshi, 2021)
Concrete cover depth largely depends on construction accuracy and is particularly affected by spacer installation accuracy. In areas where the cover depth is small, concrete spalling can occur locally due to corrosion of the reinforcing steel. Therefore, such areas should be identified in advance. In this study, the authors investigate a measuring method that can detect insufficient local coverage of concrete for middle slabs of RC rigid frame viaducts. Before examining the measurement method, the authors created a simulation, considering the variation of the concrete cover of the existing structure, to obtain the distribution of the variation of the concrete cover. Using this distribution, the authors compare the measurement accuracies of multiple cover measurement methods. The results show that it is generally possible to identify local lack of concrete cover, by conducting measurement with a rebar probe continuously in the line direction, where the distance between adjacent measuring lines is 1m or less.